(untitled) (Eurasian Scientific Herald, 2022)
To date, modern ophthalmology has not developed a single standard in approaches to the classification of DME. It is generally accepted that diabetic macular edema, as one of the manifestations of DR, can develop as ischemia and/or macular retinal edema. In DME, retinal edema always develops a second time, due to impaired capillary permeability in the macular area (lesion of the internal hemato-retinal barrier), followed by secondary damage to the retinal pigment epithelium (internal RRP) [199]. Damage to the inner and outer barriers leads to the accumulation of fluid in the macula. The consequence of these disorders is the appearance of complaints of patients about blurred central vision, the occurrence of metamorphopsia is less typical. Patients may complain about the appearance of a pinkish tint in the image, increased sensitivity to light, and there may be a cyclic decrease in visual acuity at certain times of the day (more often in the morning) [52, 87, 204, 216].